Differential phosphorylation, desensitization, and internalization of α1A-adrenoceptors activated by norepinephrine and oxymetazoline - Akinaga, Juliana [UNESP]; Lima, Vanessa [UNESP]; De Almeida Kiguti, Luiz Ricardo [UNESP]; Hebeler-Barbosa, Flávia [UNESP]; Alcántara-Hernández, Rocío; García-Sáinz, J. Adolfo; Pupo, André Sampaio [UNESP] (Elsevier, 2013)
Loss of response on repetitive drug exposure (i.e., tachyphylaxis) is a particular problem for the vasoconstrictor effects of medications containing oxymetazoline (OXY), an α1-adrenoceptor (AR) agonist of the imidazoline class. One cause of tachyphylaxis is receptor desensitization, usually accompanied by phosphorylation and internalization. It is well established that a1A-ARs are less phosphorylated, desensitized, and internalized on exposure to the phenethylamines norepinephrine (NE), epinephrine, or phenylephrine (PE) than are the a1B and a1D subtypes. However, here we show in human embryonic kidney-293 cells that the low-efficacy agonist OXY induces G protein-coupled receptor kinase 2-dependent a1A-AR phosphorylation, followed by rapid desensitization and internalization (∼40% internalization after 5 minutes of stimulation), whereas phosphorylation of α1A-ARs exposed to NE depends to a large extent on protein kinase C activity and is not followed by desensitization, and the receptors undergo delayed internalization (∼35% after 60 minutes of stimulation). Native α1A-ARs from rat tail artery and vas deferens are also desensitized by OXY, but not by NE or PE, indicating that thisproperty of OXY is not limited to recombinant receptors expressed in cell systems. The results of the present study are clearly indicative of agonist-directed a1A-AR regulation. OXY shows functional selectivity relative to NE and PE at a1A-ARs, leading to significant receptor desensitization and internalization, which is important in view of the therapeutic vasoconstrictor effects of this drug and the varied biologic process regulated by α1A-ARs. Copyright © 2013 by The American Society for Pharmacology and Experimental Therapeutics.
Keywords: adrenalin; alpha 1A adrenergic receptor; G protein coupled receptor kinase 2; noradrenalin; oxymetazoline; phenylephrine; protein kinase C; animal cell; animal experiment; animal tissue; cell strain HEK293; controlled study; drug exposure; enzyme phosphorylation; human; human cell; human tissue; internalization; male; nonhuman; priority journal; protein expression; rat; receptor down regulation; tachyphylaxis; tail artery; vas deferens; Adrenergic alpha-1 Receptor Agonists; Animals; HEK293 Cells; Humans; Male; Muscle Contraction; Norepinephrine; Oxymetazoline; Phosphorylation; Protein Binding; Rats; Rats, Wistar; Receptors, Adrenergic, alpha-1